Does economic structure determine financial structure? - Allen,HF; Bartiloro,L; Gu,X; Kowalewski,O (Journal of International Economics, 2018)
In this paper, we examine the relationship between the structure of the real economy and a country's financial system. We consider whether the development of the real economic structure can predict the direction of evolution of a country's financial structure. Using data for 108 countries, we find a significant relationship between real economic structure and financial structure. Next, we exploit shocks to the economies in India, Finland and Sweden, and South Korea and show that changes in the economic structure of a country influence the evolution of its financial system. This suggests that financial institutions and capital markets change in response to the structure of industries.